2001
DOI: 10.1016/s0004-9514(14)60297-x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational health and safety in physiotherapy: Guidelines for practice

Abstract: Most physiotherapists (91%) experience work related musculoskeletal disorders (WMSDs) at some time, and one in six makes a career change as a consequence. Many of these disorders are attributed to manual handling of patients. This paper proposes guidelines to reduce the risk of WMSDs based on Australian legislative requirements, the results of a survey of Australian physiotherapists and the literature surrounding injury prevention. These guidelines address the areas of environmental and job design, and the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
1
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 32 publications
5
35
1
3
Order By: Relevance
“…This finding suggests that physical therapists perceive work activities involving physical exertion are the most problematic factors. This finding is consistent with other studies of physical therapists [11,14,15,27,29]. This result can be explained by the specific characteristics of the physical therapists' tasks.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This finding suggests that physical therapists perceive work activities involving physical exertion are the most problematic factors. This finding is consistent with other studies of physical therapists [11,14,15,27,29]. This result can be explained by the specific characteristics of the physical therapists' tasks.…”
Section: Discussionsupporting
confidence: 92%
“…The adaptation process began with a literature review of published studies that identified ergonomic risk factors associated with the primary tasks performed by physical therapists [9,10,11,13,15,16,28,29,30,31,32,33,34,35,36]. The identification of specific risk factors supported the development and adaptation of the questionnaire items.…”
Section: Adaptation Process Of the Jfq For Physical Therapistsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Australia, the prevalence of WRMDs has been reported as being anywhere from 55% to 91% (Cromie, Robertson, and Best, 2001;West and Gardner, 2001) with Cromie, Robertson, and Best (2001) noting that one in six physiotherapists were forced to make career changes in response to injury. Most injuries occur to the low back, with the neck, upper back, wrists, and hands being the other most commonly injured areas (Bork et al, 1996;Cromie, Robertson, and Best, 2000;West and Gardner, 2001;Wajon and Ada, 2003).…”
Section: Introductionmentioning
confidence: 99%